Transforming a chemically labile (2+3) imine cage into a robust carbamate cage - Hu, Xin-Yue; Zhang, Wen-Shan; Rominger, Frank; Wacker, Irene; Schröder, Rasmus R.; Mastalerz, Michael (Chemical communications, 2017)
The synthesis of a highly acid and base-stable shape-persistent porous carbamate cage is presented. This cage is stable even in hot (100 °C) 1 M hydrochloric acid (pH = 0) or in concentrated hydrochloric acid (pH = −1) at room temperature without decomposition.